(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
he primary aim of this study was to assess the impact of implementing the flipped classroom strategy on the enhancement of critical thinking skills among secondary school students in Abha Governorate. A study was conducted on students enrolled in the secondary school at Abha Governorate to examine the potential impact of the flipped classroom strategy on their critical thinking skills in various areas, including knowledge of assumptions, interpretation, evaluation of discussions, deduction, and drawing conclusions. The study spanned a duration of one month. A total of 64 students were included in the study, with an equal distribution of 32 participants assigned to both the experimental and control groups. The research revealed a significant increase in post-test scores pertaining to critical thinking skills, namely in the areas of knowledge of assumptions, interpretation, evaluation of talks, deduction, and drawing conclusions, for the experimental group in comparison to the control group. The study also revealed that the mean scores of the experimental group on critical thinking skills, namely in the areas of knowledge of assumptions, interpretation, evaluation of talks, deduction, and drawing conclusions, showed a significant improvement from pre-measurement to post-measurement. There is no statistically significant difference observed between the scores of the experimental group and the control group in terms of critical thinking skills, namely in the areas of understanding of assumptions, interpretation, evaluation of discussions, deduction, and drawing conclusions, immediately after the intervention and during the follow-up assessment.